Eco design for Ag-based solutions against SARS-CoV-2 and E. coli. Issue 11 (17th October 2022) - Costa, Anna Luisa; Blosi, Magda; Brigliadori, Andrea; Zanoni, Ilaria; Ortelli, Simona; Simeone, Felice Carlo; Delbue, Serena; D'Alessandro, Sarah; Parapini, Silvia; Vineis, Claudia; Varesano, Alessio; Toprak, Muhammet S.; et al.
Abstract : An effective, eco-friendly and easily scalable nanosilver-based technology offers affordable and broad-spectrum antimicrobial solutions against SARS-CoV-2 and Escherichia coli . Abstract : For the first time, we exploited the antiviral and antibacterial properties of Ag NPs stabilised by quaternized hydroxyethyl cellulose (Ag-HEC) against SARS-CoV-2 and Escherichia coli through an eco-friendly process at room temperature in three different environments: 1) water, where Ag was dispersed as a nanosol, 2) textiles, where Ag was applied as a coating, and 3) hydrogel where Ag is embedded. The antiviral performance of Ag-HEC nanosols was quantified through the selectivity index (SI), defined as the ratio between 50% cytotoxic and inhibitory concentration, in order to evaluate the ability to be active in a concentration range below the cytotoxicity value. The collected results pointed out an actual enhanced risk/benefit profile of Ag-HEC NPs with respect to chloroquine, with an SI of 22.2 and 8.4, respectively. Antibacterial and antiviral activities of Ag-HEC NPs immobilized on textiles or mucosa-like hydrogels were also assessed and their efficacy in potential application as protective clothing or nasal molecular masks was verified. This work demonstrated that a modern, safe and sustainable design allows traditional colloidal silver-based technologies to be efficiently exploited for a broad spectrum of antimicrobial solutions against bacterial and viral infections.